NURSE PROFESSION STUDENTS’ EXPERIENCES ON EXIT EXAMINATION PREPARATION: A QUALITATIVE STUDY - Jessica Novia Christi; Tambunan, Evelyn Hemme (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Exit examination is a mandatory requirement for nurse profession students, making it crucial to understand their experiences during preparation. This qualitative study aims to explore the experiences of nurse profession students in preparing for their exit examinations, a critical component in their transition from academic learning to professional practice. Using in-depth interviews with six nurse profession students from Universitas Advent Indonesia, Bandung, the research investigates the physical, psychological, spiritual, social and economic aspects that influence their preparation process. The findings reveal the themes of physical health, mental strength, spiritual practices, social connections and financial challenges. These findings underscore the importance of addressing the holistic needs of nurse profession students during exit examination preparation and suggest that a balanced approach encompassing physical, mental, spiritual, social and economic support can enhance student well-being and improve examination outcomes.